Gender differences in neurocognitive impairment among first-episode, drug-naïve schizophrenia patients: a cross-sectional study - Qing Zhang; AiMin Sui; Min Su; MingLiang Ju; YanYan Wei; XiaoChen Tang; LiHua Xu; HuiRu Cui; YingYing Tang; ZhengHui Yi; HaiChun Liu; Jin Gao; et al. (Frontiers in Psychiatry)
IntroductionCognitive impairment is a core feature of first-episode schizophrenia (FES), yet the influence of biological sex on its manifestation remains under characterized. Existing evidence suggests sex differences in cognitive profiles among chronic schizophrenia patients, but whether these patterns emerge in drug-naïve FES patients—and how they relate to clinical symptoms—requires clarification.MethodsWe recruited 382 drug-naïve FES patients and 522 healthy controls (HCs) matched for age and education. Cognitive function was assessed using the MATRICS Consensus Cognitive Battery (MCCB). Clinical symptoms were evaluated via the Positive and Negative Syndrome Scale (PANSS).ResultsFES patients demonstrated global cognitive deficits compared to HCs. When stratified by diagnostic group (FES and HC), males outperformed females in planning and problem-solving, as measured by the Neuropsychological Assessment Battery Mazes subtest (p < 0.001), whereas females showed superior performance in visuospatial memory, as assessed by the Brief Visuospatial Memory Test–Revised (p < 0.001) in both groups. When stratified by gender, FES patients exhibited similar patterns of impairment severity relative to their gender-matched HCs: both male and female FES patients showed the most pronounced deficits in processing speed (BACS) and sustained attention (CPT), with effect sizes of 1.64 and 1.52 for males, and 1.36 and 1.48 for females, respectively. Correlational analyses revealed that male FES patients’ cognitive impairments were specifically associated with negative symptoms, while female impairments correlated broadly with all PANSS domains. Correlational analyses revealed that in FEP patients, male cognitive impairments were specifically associated with negative symptoms, while female impairments showed broad associations with all domains of the PANSS.ConclusionFES manifests as sex-divergent cognitive profiles, with males showing executive/processing speed deficits tied to negative symptoms and females exhibiting memory impairments with broader symptom associations. These findings underscore the need for sex-sensitive approaches in characterizing cognitive dysfunction in early psychosis.